Penanaman nilai-nilai karakter tanggung jawab melalui Pembelajaran Pendidikan Pancasila di kelas IV Madrasah Ibtidaiyah Negeri 1 Serang - Siti Qurotul Aini; Ratna Sari Dewi; Damanhuri (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Babunnajah Pandeglang, 2025)
This study aims to determine how the process of instilling character values of responsibility through Pancasila Education learning. The research method used is descriptive qualitative, data collection techniques in this study through interviews, observation, and documentation. The subjects in this study were class teachers, head of madrasah, and students of class IV/A & C MIN 1 Serang. The character of responsibility is instilled as early as possible for the good of students in the future, so that students become people who can be trusted and are able to lead society towards a better civilisation because in their hands the future of the nation is entrusted. The results showed that, 1) the implementation of the character values of responsibility carried out by the teacher is by integrating the character of responsibility with the material being taught, 2) Evaluation of the cultivation of the character value of responsibility through Pancasila Education learning is done by assessing the attitude of students through habituation that is routinely held in class and outside the classroom, 3) the challenges faced by teachers in instilling the character of responsibility are still lack of facilities and infrastructure and still lack of cooperation between teachers and parents of students in instilling the character of responsibility.